Organic Chemistry in Portugal from 1900 to 1970: A Contribution to the History of Science - Martins, Paulo Nuno (Orbital: The Electronic Journal of Chemistry, 2017)
The main purpose of this article is to describe the contributions made by various professors in Portuguese institutions, (located at Lisbon, Coimbra and Oporto), for the development of organic chemistry, between 1900 and 1970, so that we can get a better idea of the Portuguese work done in this area (i.e., teaching, pedagogical, etc.). For this purpose, we will take particular attention to technical books used in class (lecture and laboratory). Another point of this article is to refer the organic chemistry laboratories, existent in various Portuguese universities, in order to understand the importance of practice for the complete university student training. DOI: http://dx.doi.org/10.17807/orbital.v9i5.1086